Vitamin B12 absorption after necrotizing enterocolitis. Issue 8 (August 1984) - Collins, J E; Rolles, C J; Sutton, H; Ackery, D
Abstract : Resection of the terminal ileum for necrotizing enterocolitis is not uncommon in neonates requiring intensive care in the first weeks of life. They may therefore be at risk of vitamin B12 malabsorption, and later of vitamin B12 deficiency. A method of measuring B12 absorption is described and the results are given. This assessment should be part of the follow up for all these children.